Forests in Fragile and Conflict-Affected States - Harwell, Emily (Washington, DC: World Bank, 2012)
Recognizes in failed states or states at risk of becoming failed states the linkages between forests, armed conflict, poverty, and various aspects of state fragility. Forests are valuable for local subsistence livelihoods, timber, and other commercially valuable forest products, as well as ecosystem services including forest carbon and biodiversity. This makes the linkage between forests and fragile states significant to local poverty reduction, national and global trade, and global public goods. Certain aspects of timber offset this propensity toward violence: (1) because timber has a low value to weight ratio and is difficult to smuggle due to size, it does not contribute to prolonging violence for its economic worth; (2) timber does not experience price volatility like precious minerals; and (3) end users of timber look at its sourcing and want certification of legality. Long-term commitment to protect and replant forests is important in post-conflict periods during which time government and donors can isolate spoilers and work for change through interagency and public participation.